Socio-Cultural Based Religious Moderation Among the Young Muslim Generation in Arjawinangun Cirebon - Aisyah Nurjanah; Annisa Situmorang; Erni Haryanti (Glosains: Jurnal Sains Global Indonesia, 2024)
Indonesia's diverse society demands a tolerant attitude. However, it is a paradox in Indonesia's diverse society that the emergence of intolerant attitudes, radicalism and extremism, especially those targeting the millennial generation, is fearful, for this reason it is necessary to build a moderate understanding. From this background, researchers are interested in examining socio-culturally based religious moderation in the millennial generation in Arjawanangun Cirebon. Researchers use qualitative field methods with a phenomenological approach. Religious moderation occurs in the socio-cultural aspects of society, such as participating in social, religious, youth activities, commemorating national holidays, weddings, while still paying attention to the limits of tolerance. Karang Taruna organizations are a forum for interfaith youth interaction. The religious tolerance of the millennial generation cannot be separated from the role of education in the family which has been instilled by their parents.